2020
DOI: 10.1103/physrevlett.124.127201
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Rotation of Ferrimagnetism Driven by Antiferromagnetic Spin Canting

Abstract: Spin-reorientation phase transitions that involve the rotation of a crystal's magnetisation have been well characterised in distorted perovskite oxides such as the orthoferrites. In these systems spin reorientation occurs due to competing rare earth and transition metal anisotropies coupled via f − d exchange. Here, we demonstrate an alternative paradigm for spin reorientation in distorted perovskites. We show that the R2CuMnMn4O12 (R = Y or Dy) triple A-site columnar ordered quadruple perovskites have three o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…A study by Vibhakar et al [42] on triple A-site columnar-ordered quadruple perovskites has shown that the mechanism behind SR in these structures is the competition between DMI and SIA, which is similar to the mechanism that we found to be at play in RM O 3 's SR.…”
Section: Origin Of the Slow γ4 To γ2 Rotationsupporting
confidence: 83%
“…A study by Vibhakar et al [42] on triple A-site columnar-ordered quadruple perovskites has shown that the mechanism behind SR in these structures is the competition between DMI and SIA, which is similar to the mechanism that we found to be at play in RM O 3 's SR.…”
Section: Origin Of the Slow γ4 To γ2 Rotationsupporting
confidence: 83%
“…The refined magnetic structure is consistent with the collinear ferrimagnetic phase found in Tm 2 MnMnMn 4 O 12 [17] and R 2 CuMnMn 4 O 12 [18]. Moment orientations of m||[x, 0, 0], m||[x, x, 0], or m||[x, y, 0] correspond to different magnetic symmetries described by the three distinct order-parameter directions of the + 5 irrep (see Tables III, IV, and V of Appendix A); however, these three cases cannot be differentiated by our neutron-diffraction data due to powder averaging in the tetragonal crystal symmetry.…”
Section: (A)supporting
confidence: 80%
“…The prevalence of spin fluctuations is emerging in the wider family of A-site columnar ordered quadruple perovskites that support competing exchange pathways. For example, in R 2 CuMnMn 4 O 12 (R = Y or Dy), B-site Mn 3+ moments appear to saturate at 3 4 of their theoretical value, and only on cooling through a low-temperature phase transition, proposed to originate in the softening of low-energy magnons, do they recover their full moment [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spin reorientation should occur via competition between DMI and other energy terms such as Heisenberg exchange interaction, magneto‐crystalline anisotropy, and magnetostatic energy. [ 39–41 ] It is natural to see the transition from the helimagnetic spin alignment to the commensurate state due to the competitions. Since all those energies are T dependent, quantitative study for each energy parameter is required to manifest exact origin of the large‐range cusp.…”
Section: Resultsmentioning
confidence: 99%